Acute phase responses in clinically healthy multiparous Holsteins with and without calcium dysregulation during the early postpartum period - J.A. Seminara; C.R. Seely; J.A.A. McArt (Journal of Dairy Science)
ABSTRACT: Patterns of calcium dysregulation resulting in low total serum calcium concentrations (tCa) at 4 DIM, known as dyscalcemia, commonly occur in multiparous Holsteins. Dyscalcemia is associated with risk of disease, decreased production, and poor reproductive performance. Inflammation is well-documented early in lactation and is associated with similarly suboptimal outcomes. The acute phase response produces markers and mediators of inflammation; therefore, the objective of our case-control study was to evaluate postpartum patterns of 3 positive acute phase proteins in cows with and without dyscalcemia. We hypothesized that dyscalcemic cows would experience more activated inflammation than eucalcemic cows and that inflammation would precede dyscalcemia diagnosis. Multiparous Holstein cows at 2 commercial dairy farms in central New York were enrolled from a parent study based on tCa at 4 DIM, at a 2:1 ratio of eucalcemic (tCa >2.3 mmol/L; n = 32) to dyscalcemic cows (tCa <2.2 mmol/L; n = 16). Blood was collected 1 to 3 d before parturition and once every 24 h postpartum through 4 DIM. Samples were analyzed for 3 acute phase proteins, serum amyloid A (SAA), haptoglobin and LPS binding protein (LBP). Patterns of protein concentrations in blood over time were compared using linear mixed effects models including fixed effects of calcium status group, time, parity group, farm, relevant 2-way interactions, and the random effect of cow. Overall, dynamics of acute phase proteins showed that dyscalcemic cows experienced increased acute phase responses compared with eucalcemic cows, and that these responses preceded dyscalcemia diagnosis at 4 DIM. Dyscalcemic cows had elevated concentrations of SAA beginning at 2 DIM (eucalcemic: mean = 13.88 µg/mL, 95% CI = 11.34 to 16.99 µg/mL; dyscalcemic: mean = 32.95 µg/mL, 95% CI = 24.55 to 44.21 µg/mL) and continuing through 4 DIM (eucalcemic: mean = 8.14 µg/mL, 95% CI = 6.66 to 9.95 µg/mL; dyscalcemic: mean = 30.01 µg/mL, 95% CI = 22.60 to 39.83 µg/mL). Haptoglobin concentrations were also elevated in the blood of dyscalcemic cows from 2 DIM (eucalcemic: mean = 0.39 g/L, 95% CI = 0.31 to 0.49 g/L; dyscalcemic: mean = 1.11 g/L, 95% CI = 0.79 to 1.56 g/L) through 4 DIM (eucalcemic: mean = 0.27 g/L, 95% CI = 0.21 to 0.34 g/L; dyscalcemic: mean = 1.65 g/L, 95% CI = 1.19 to 2.28 g/L). Concentrations of LBP exhibited a different pattern with a small difference between groups at 3 DIM (eucalcemic: mean = 4.67 µg/mL, 95% CI = 4.02 to 5.42 µg/mL; dyscalcemic: mean = 7.91 µg/mL, 95% CI = 6.49 to 9.63 µg/mL) that became larger at 4 DIM (eucalcemic: mean = 4.88 µg/mL, 95% CI = 4.22 to 5.64 µg/mL; dyscalcemic: mean = 10.79 µg/mL, 95% CI = 8.84 to 13.17 µg/mL). Our work supports the hypothesis that dyscalcemia and inflammatory activity are associated in dairy cows under naturally occurring postpartum conditions. Although the causal structure of this relationship remains unknown, improved understanding of inflammation and dyscalcemia may provide insight into mechanisms by which some cows experience maladaptation during the early postpartum period.